IMPLEMENTASI MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PADA MATERI ENERGI ALTERNATIF SISWA KELAS VA SD INPRES KAPASA - Wahyuni, Ariska Sara Reski; Hikmah Marisda, Dewi; Muafiah Nur, Andi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students' cognitive learning outcomes on alternative energy material through the application of the Problem Based Learning (PBL) model for 5th-grade students at SD Inpres Kapasa. The background of this study is the low learning outcomes caused by conventional teaching methods and lack of active student engagement in solving contextual problems. This study is Classroom Action Research (CAR) using the Kemmis and McTaggart model conducted in two cycles, involving planning, acting, observing, and reflecting. The subjects were 16 students. Data were collected through observation, tests, and documentation. The results showed that in cycle I, the students' average score was 63.4 with 56.2% classical mastery. After improvements in cycle II, the average score increased to 91.2 with 93.7% classical mastery. It can be concluded that the application of the Problem Based Learning model is effective in improving students' cognitive learning outcomes in science on alternative energy material in 5th grade at SD Inpres Kapasa.